PEMBERDAYAAN KELUARGA DALAM DETEKSI DAN STIMULASI TUMBUH KEMBANG BALITA - Ari Sulistyawati; Dinda Ayu Amalia; Nila Ayu Anggraini (LPPM STIKES Madani Yogyakarta, 2019)
Development of under five children is an indicator of their health status in the future, so we need to monitor the process. Detection of irregularities must be known by all parties involved. Family Groups of under five children in Dusun Karanganom have difficulty in detecting and stimulating growth and development. Families also experience problems, including 1) Children have less willingness to eat and parents have not found a solution to overcome the problem, 2) Achievement of child development in gross and fine motoric aspects is not suitable for their age, 3) Special activity for under five children (Posyandu) is limited only in measuring weight as one of growth indication. A training had been carried out for Family Groups in Dusun Karanganom, Sitimulyo Village, Piyungan District, Bantul Regency, DIY. The implementation was conducted for four weeks during April 2018. The purpose of the training is to increase the independence of the family of under five children in detecting and stimulating their children’s growth. The method of implementing this service was carried out in several stages, namely: 1) the preparation , 2) socialization, 3) guidance, and 4) counseling stages. The results of this service can be seen from the increase of the family interest about the task and achievement of child development based on their age, how to detect child growth and development, and stimulation techniques for child development. Karanganom Toddler Family Groups want to able to monitor the ability of the family to detect and stimulate the growth and development of children on an ongoing basis.